Preferensi Konsumen Pindang Di Kabupaten Ogan Ilir - Karo Karo, Pelliyezer (Jurnal Akademi Pariwisata Medan, 2025)
This study aims to describe the culinary potential of pindang in Ogan Ilir Regency as an alternative gastronomic tourism which can be one of the tourist attractions. This research was carried out observantly with descriptive and analytical survey methods. The primary data in this study was obtained from the respondents' answers to a series of questions through questionnaires built and interviews conducted. The descriptive analysis was used to produce statistics on the frequency of respondent data in 2 categories, namely based on demographics and behavior. The characteristics of the work are divided into four groups (ASN/TNI/POLRI/BUMN-BUMD), private employees, self-employed/entrepreneurs and students; and the category of residence location is divided into 4 groups. The results of this consumer preference research showed that the dominance of 84 percent of respondents preferred to pay in cash or cash, while the other 12 percent made payments with the choice of banking QRIS. The preference of consumers was influenced by the following factors: (i) the preferences of consumers were divided into two categories: (1) the preference of a restaurant or restaurant, (2) the preference for a food product, and (3) the preference to eat a meal. In this research, there were three main inputs that can be aimed at managers or owners of restaurants or pin-dang restaurants.